Do Standard Real Option Models Overestimate the Required Rate of Return of Real Estate Investment Opportunities? - Luis H. R. Alvarez; Jukka Lempa; Elias Oikarinen (Aboa Centre for Economics (ACE), 2009)
We consider how the inter-temporal discreteness of the revenue and cost processes affect the optimal timing of a real estate investment opportunity in comparison with the investment timing strategy obtained by relying on the traditional continuous real option model. We characterize both optimal investment rules explicitly and show that the continuous model may lead to a significantly higher required rate of return than the discrete model. Hence, our results show that the use of continuous time models leads to smaller and suboptimal amount of investment. Our numerical illustrations also indicate that this difference grows as volatility increases. Consequently, even though higher volatility decelerates investment in the discrete case as well, it decelerates it less than the continuous model would predict.
Keywords: G11; R31; C44; 330; Real options; real estate investment timing; exchange option